Control system of gas-turbine engines condition in operation - Кулик, Н. С.; Кучер, А. Г.; Тарасенко, А. В. (Proceedings of National Aviation University (archive), 2000)
The main problems of construction of automatized control systems of gas-turbine engines condition in operation are considered